213k views
0 votes
How do i solve this? please help.

5x - 6 - 2x = 3 ( x - 2 )

2 Answers

0 votes
5x-6-2x=3(x-2)
3x-6=3x-6
3x-6-3x=3x-6-3x
-6=-6
This is infinitely many solution. X can be any number

Hope this will help!!
User Ankit Raonka
by
5.7k points
5 votes

Answer:

Infinite Solutions

Explanation:

Distribute the 3 by multiplying it to the two terms on the right side.

5x - 6 - 2x = 3x - 6

Isolate the x value to the left and move the other terms to the right.

5x - 2x - 3x = 6 - 6

Combine all like terms.

3x - 3x = 0

0x = 0

All numbers multiplied by zero is still zero, so this equation has infinite solutions.

User Jmroyalty
by
5.6k points